Interações sociais no ambiente virtual de aprendizagem : análise de linguagem de feedbacks - Rabello, Márcia Rodrigues (2011)
With the introduction of new technologies of information and communication in education, interaction among individuals of the process in Virtual Learning Environments (VLE) it is essential to appropriate mediators elements, also known as digital resources available in virtual spaces. In this context, the conception of appropriated teaching strategies to this setting may allow students learn more collaboratively. This research, quantitative in character, descriptive, exploratory and ethnographic guided by the following question: how the digital resources available on the VLE provide social interaction among individuals in the context of ODL? This study aims to identify the potential of digital resources available on the VLE of Faculdade Meridional (IMED) from Passo Fundo/RS, analyzing the extent to which these resources provide ways of interaction for teachers to mediate the knowledge´s construction of students. To this end, this work is based on the intersection of the concept of interaction/mediation proposed by Lev Vigotsky, in his socio-historical theory. In the systematic analysis of the resources and strategies used in virtual classrooms, profiles of teachers and students, the available elements in virtual classes, more frequently used resources, the feedback of virtual activities, as well as used forms of synchronous and asynchronous communication are examined. Rather than make a suggestion related to the use of digital resources available on the VLE to promote interaction, this dissertation sewing a series of reflexions related to the teaching-learning process in the virtual context and interaction among individual present in the educational setting, emphasizing that the different ways of interaction and mediation are fundamental for the educational process of XXI century. Keywords: